Іmplementation of the politeness principle and evasion strategy in the texts of conversations and interviews with I. Brodsky - Mikhalchuk, Natalya A. (Journal of the Belarusian State University. Philology, 2020)
Some aspects of the problem of language personality specificity of I. Brodsky are analyzed ‒ the implementation of the principle of politeness of G. Leech and also analysis of the strategy of evasion in the texts of conversations and interviews with the poet. It is proved that in oral speech I. Brodsky correctly observes the maxims of approval and modesty in the framework of the principle of politeness of G. Leech. It is justified that the object of approval can be both the interlocutor and third parties, moral and aesthetic assessments are differentiated. In addition to the actual approval, in the oral speech of I. Brodsky the intention of non-condemnation is evident. It is noted that the poet uses the indirect way of expressing approval and condemnation less often than the direct one. The specific features of Brodsky’s speech behavior are the use of complex interpretative subjective statements and evasive answers. In I. Brodsky’s discourse a special kind of evasion is distinguished, this is an appeal to his artistic creativity.